Bending properties of finger jointed from oil palm lumber (OPL) / Izwan Ismail - Ismail, Izwan (2012)
This research is to determine the bending properties (modulus of elasticity (MOE) and modulus of rupture (MOR) of finger jointed from oil palm lumber (OPL). OPL have been used because of the potential as raw material to replace the solid wood that is becoming short in supply in future. Oil palm lumber from peripheral zone at different portion top, middle and bottom is taken to produce finger joint in different type of finger orientation which is vertical and horizontal. From the result, it can be concluded that MOR and MOE of the bottom portion is higher compared to middle and top portion. Increase in density caused increases the MOR and MOE value. The strength for horizontal and vertical finger joint is little bit different even through both MOR and MOE graphs showed the strength of horizontal finger joint is a bit higher than the vertical finger joint.